2011
DOI: 10.1002/bit.23148
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxybutyrate production from lactate using a mixed microbial culture

Abstract: In this study we investigated the use of lactate and a lactate/acetate mixture for enrichment of poly-3-hydroxybutyrate (PHB) producing mixed cultures. The mixed cultures were enriched in sequencing batch reactors (SBR) that established a feast-famine regime. The SBRs were operated under conditions that were previously shown to enable enrichment of a superior PHB producing strain on acetate (i.e., 12 h cycle length, 1 day SRT and 30°C). Two new mixed cultures were eventually enriched from activated sludge. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 140 publications
(103 citation statements)
references
References 50 publications
4
88
1
4
Order By: Relevance
“…In previous acetate-fed SBRs that were dominated by P. acidivorans and operated at volume exchange ratios between 0.04 and 0.50 (1-12 h cycles) the feast phase occupied around 5% of the total cycle ( Fig. 7) (Jiang et al, 2011a(Jiang et al, , 2011b. At an exchange ratio of 0.75 (18 h cycles) the relative feast phase length increased to 12%.…”
Section: Impact Of the Exchange Ratiomentioning
confidence: 87%
See 4 more Smart Citations
“…In previous acetate-fed SBRs that were dominated by P. acidivorans and operated at volume exchange ratios between 0.04 and 0.50 (1-12 h cycles) the feast phase occupied around 5% of the total cycle ( Fig. 7) (Jiang et al, 2011a(Jiang et al, , 2011b. At an exchange ratio of 0.75 (18 h cycles) the relative feast phase length increased to 12%.…”
Section: Impact Of the Exchange Ratiomentioning
confidence: 87%
“…Johnson et al (2009a) presented three accumulation experiments -conducted after respectively 2, 7, and 16 months of operation -that show a clear increase of the biomass-specific PHB production rate and the PHB storage capacity over time. Furthermore, the feast phase was reported to last 50 min (Johnson et al, 2009a), while later a feast phase length of 38 min has been reported for the same enrichment culture (Jiang et al, 2011b).…”
Section: Enrichment Progressmentioning
confidence: 88%
See 3 more Smart Citations